Laparoscopic regional radical hysterectomy showed promising clinical outcomes in early-stage cervical cancer - Weihong Yang; Rong Chen; Caixia Li; Li Li; Ning Luo; Zhongping Cheng (Wolters Kluwer Medknow Publications, 2020)
Objectives: To evaluate the clinical outcomes of standardized and region-specific excision in laparoscopic radical hysterectomy (LRH) for early-stage cervical cancer (ECC). Materials and Methods: This is a retrospective case-controlled study from 2011 to December 2016. A total of 328 women with ECC (IA1, IA2, IB1, or IIA1) underwent primary surgery by laparoscopy or laparotomy in our institute. Women diagnosed as stage IB1 or IIA1 were treated with radical hysterectomy (RH) by open or laparoscopic route. The total parametrium excision in the process of RH was measured and highlighted in the study. Results: A total of 186 patients underwent open surgery and 142 ones were treated with laparoscopic surgery. Laparoscopic surgery was associated with less blood loss (194.43 ± 84.40 ml vs. 362.68 ± 253.36 ml, P < 0.01), shorter hospital stay (11 vs. 14 days, P < 0.01), and lower risk of blood transfusion (2.8% vs. 18.8%, P < 0.01). There was no significant difference in the postoperative complications between two groups (18/142, 12.7% vs. 21/186, 11.3%; P > 0.05). The rate of 5-year overall survival (OS) was 92.8% in laparoscopy group, similar to that of 94.4% in the open group (P = 0.762). Disease-free survival (DFS) rate at 3 years in laparoscopy group was decreased when compared to open group (91.8% vs. 95.0%, P = 0.030), but there was no significant difference in 3-year DFS among the women with tumor size <2 cm (100% vs. 97.0%, P = 0.818). Conclusion: Laparoscopic surgery was associated with better surgical outcomes compared to open surgery in ECC. 5-Year OS was comparable between the groups and cases with tumor size <2 cm showed no difference in 3-year DFS. LRH may be a better fit for women with tumor size <2 cm. Standardized region-specific RH helps to optimize the clinical outcomes of LRH in ECC.